MENENTUKAN BESAR MEDAN LISTRIK RADIAL PADA BERBAGAI JENIS KONDUKTOR YANG DIALIRI ARUS LISTRIK TETAP - Suhandi, Andi; Rusdiana, Dadi; Kaniawati, Ida; Mudjiarto, R (Faculty of Mathematics and Science Education, Universitas Pendidikan Indonesia, 2002)
A typical example in courses on electricity and magnetism is that of a conductor carrying a steady current. It is said that the electric field inside the conductor is parallel to the current and that there is no transverse (radial) component of the field. While this is reasonable assumption justified for pedagogical purposes, it is not rigorously true. In this paper, the transverse electrical field is calculated as being different from zero, but negligible from an experimental point of view. For various conductors, the transverse electrical field is a polynomial function from steady current.